Yield improvement and yield variability reduction in an EOQ model with planned shortages and random yield. (October 2015) - Paknejad, Javad; Nasri, Farrokh; Affisco, John F.
Highlights: Three models for improving yield rate and reducing yield variability are developed. The optimal values of the policy variables and costs are presented in explicit form. In all three models investment programs lead to yield improvement and cost savings. Abstract: This paper reports the results of an investigation of a set of continuous time, constant demand inventory models under the condition of yield uncertainty. Specifically, the impact of yield improvement programs on lot size, backorder level, and the resulting costs are examined. Models for improving yield rate and reducing yield variability are developed and examined through a series of numerical exercises. In addition, a model for the simultaneous improvement of yield rate and yield variability is presented for the case where there is a relationship between the mean and variance of the yield distribution. In all cases, investment programs improve the picture with respect to manufacturing yield for processes which are not necessarily under statistical control.